Cystic Fibrosis: The Sense of Smell. Issue 1 (January 2020) - Di Lullo, Antonella M.; Iacotucci, Paola; Comegna, Marika; Amato, Felice; Dolce, Pasquale; Castaldo, Giuseppe; Cantone, Elena; Carnovale, Vincenzo; Iengo, Maurizio
Background: Cystic fibrosis (CF) is a multisystem disease that involves the upper airways with chronic rhinosinusitis (CRS) causing nasal congestion, rhinorrhea, mouth breathing, facial pain, and olfactory dysfunction. Twelve percent to 71% of CF patients report smelling alterations with an impact on nutrition and quality of life. Objectives: The goal was to study olfaction performance in CF patients with CRS that worsens quality of life. Methods: A total of 121 subjects were enrolled in this study. Seventy-one had CF and underwent ear, nose, and throat evaluation with nasal endoscopy, sinonasal outcome test 22 (SNOT-22), visual analog scale (VAS), and "Sniffin' Sticks." Fifty subjects were age-matched with healthy controls. Results: All 71 CF patients were affected by CRS; 59 of 71 (83.1%) had CRS without nasal polyps and 12 of 71 (16.9%) had CRS with early nasal polyps. None of the 50 controls had CRS. Total SNOTT-22 mean values in the 71 CF patients were 38.10 ± 21.08 points. If considering only the 59 CF patients without nasal polyps, the SNOTT-22 mean value was 36.76 ± 21.52 points. Moreover, based on the VAS scores, the degree of nasal symptoms was classified as mild for facial pain, smell alteration, nasal discharge, and sneezing and resulted in moderate symptoms for nasal blockage and headache. Among the CF patients, 55 of 71 (76.5%) declared to be normosmic, while the smelling ability assessed by "Sniffin' Sticks" showed that only 4 of 71 (5.63%) were normosmic, 58 (81.69%) were hyposmic, and 9 (12.68%) were anosmic. In the controls, 41(82%) were normosmic, 9 (18%) were hyposmic, and none were reported to be anosmic ( P  < .001). Conclusions: We confirm that most CF patients have a relevant olfactory impairment, although only a low percentage declares such alteration. A careful evaluation with simple and rapid tests helps to select the patients who may benefit from specific therapies.